1991
DOI: 10.1111/j.1432-1033.1991.tb15963.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of hepatic proteolysis by amino acids

Abstract: 1. Proteolysis in isolated perfused rat liver was monitored as [3H]leucine release into effluent perfusate after in vivo labeling by intraperitoneal injection of [3H]leucine about 16 h prior to the perfusion experiment. Exposure of the livers to hypotonic perfusion media (175 -295 mOsmol . 1-I) increased liver mass due to cell swelling and inhibited [3H]leucine release. The extent of inhibition of [3H]leucine release was linearly related to the liver-mass increase, regardless of whether livers from fed or 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…As autophagic proteolysis is strongly dependent on lysosomal pH, the intravesicular alkalinization observed here could well participate in the anti-proteolytic effects of cell swelling after treatment with glutamine, barium and reduction of extracellular osmolarity (Haussinger et al, 1990a(Haussinger et al, , 1991Hallbrucker et al, alkalinization occurring after cell swelling is not restricted to a minor portion of acidic compartments. As lysosomes constitute a major portion of acidic intracellular compartments (Tager et al, 1988), it appears very unlikely that intravesicular alkalinization following cell swelling does not include lysosomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As autophagic proteolysis is strongly dependent on lysosomal pH, the intravesicular alkalinization observed here could well participate in the anti-proteolytic effects of cell swelling after treatment with glutamine, barium and reduction of extracellular osmolarity (Haussinger et al, 1990a(Haussinger et al, , 1991Hallbrucker et al, alkalinization occurring after cell swelling is not restricted to a minor portion of acidic compartments. As lysosomes constitute a major portion of acidic intracellular compartments (Tager et al, 1988), it appears very unlikely that intravesicular alkalinization following cell swelling does not include lysosomes.…”
Section: Discussionmentioning
confidence: 96%
“…The intracellular mechanisms mediating this effect, however, have remained elusive until recently, when it has been recognized that cell swelling, as it occurs during the concentrative uptake of amino acids, markedly inhibits proteolysis (Hiiussinger et al, 1990b(Hiiussinger et al, , 1991 Hiiussinger and Lang, ,b, 1992Hallbrucker et al, 1991a). It has been shown that the anti-proteolytic effect of glutamine, for instance, is fully mimicked by proportionate cell swelling due to reduction of the extracellular osmolarity or inhibition of the action of K+ channels in the cell membrane (Hiiussinger et al, 1990b(Hiiussinger et al, , 1991Lang, 1991a,b, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although amino acids are known to be inhibitors of hepatic autophagic proteolysis, very little information is available regarding the mechanism by which they exert this effect [32, 331. In their stimulating studies on the control of proteolysis in the isolated perfused liver, Haussinger and coworkers [7,[9][10][11] recently proposed that the increase in cell volume following amino-acid influx is in part responsible for the inhibition of proteolysis by amino acids. They not only demonstrated that perfusion with hypo-osmotic media was able to mimic the anti-proteolytic effect of amino acids, but also that the inhibitory effect of several amino acids (but not all of them) could be directly attributed to their ability to induce cell swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic proteolysis is under the control of amino acids, hormones ( [1][2][3][4]; for reviews see [5,6]) and liver cell volume [7,8]. The mechanisms underlying proteolysis control by amino acids and hormones are not understood [6]; however, recent evidence points to an involvement of cell volume alterations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying proteolysis control by amino acids and hormones are not understood [6]; however, recent evidence points to an involvement of cell volume alterations [7][8][9]. The anti-proteolytic effects of glutamine and glycine could be fully mimicked by equipotent hypo-osmotic cell swelling [7,8], and the inhibition of proteolysis by other amino acids could, at least in part, be ascribed to amino acid-induced cell swelling [8]. The anti-proteolytic effect of insulin in liver parallels the extent of hormone-induced intracellular K+ accumulation, even when the insulin-induced K+ uptake was modulated by the nutritional state or a variety of inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%